Meluruskan Logika Pemerintah Soal Kegentingan Moratorium UU Kepailitan dan PKPU - Serlika Aprita (UIN Syarif Hidayatullah Jakarta, 2022)
The discussion that emerged from the moratorium on the Bankruptcy Law and the PKPU, all forms of changes to regulations are the absolute right of the Government which of course, before issuing the policy, the Government has considered and reviewed all inputs from stakeholders. As the main purpose of the decision is in the public interest. the concept of PKPU and bankruptcy only by considering the indications of “Moral Hazard” that may arise in the process. The spirit of business continuity adopted by the Bankruptcy Law and PKPU must be taken into consideration because it has been proven to have saved several debtors from business destruction. The imposition of a moratorium is not the only way out to avoid the threat of